KALIMAT MINOR DALAM ACARA KICK ANDY - Larosa, Erni Fajar; Auzar, Auzar; Charlina, Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research are to explain the types and the forming meaning context of some minor sentences used in Kick Andy talk show. The type of this study is qualitative research with descriptive method. The source of the data as the object of the research is Kick Andy talk show in Metro TV. The data collection tecnique was done by using observing note taking tecnique the 5 episode in February to early March 2018 of Kick Andy talk show in different topics. The result of the research showed that there were 5 types of unstructured minor sentences which is used in; calling, greeting, the title, ordering expression, ordering instruction, and the type of structured minor sentences elips and marginal sentences.The context forming the meaning of minor sentences were known and analyzed based on pragmatics side by using contextual meaning theory. The context forming the meaning of minor sentences is based on the context of linguistic contexts, emotional contexts, situational contexts, cultural contexts, contexts of context, contexts of context, formal contexts of speech, contexts of moods of speakers / listeners, time context, place context, object context , the context of completeness of speech / hearing, speaker / listener context, or language context.Key Words: minor sentences, talk show, kick andy.